Diversifying Cross‐Coupling Strategies, Catalysts and Monomers for the Controlled Synthesis of Conjugated Polymers. Issue 50 (25th June 2018) - Baker, Matthew A.; Tsai, Chia‐Hua; Noonan, Kevin J. T.
Abstract: Chain‐growth polymerization of aromatic building blocks (termed catalyst‐transfer polycondensation or CTP) has emerged as a powerful method for the controlled synthesis of conjugated polymers. CTP affords semiconducting materials with predictable molecular weights, relatively narrow molar mass distributions and tailored backbone compositions (e.g. blocks, gradients, stars). Homogeneous catalysis utilizing transition metals has played a critical role in the rise of this field and this Minireview is designed to highlight some of the catalysts employed for these polycondensations. Some descriptions of the metal and ancillary ligands are included, along with which catalysts have been used for different aromatic monomers. Cross‐coupling strategies are discussed briefly for ease of use. Finally, some potential future directions are described for further evolution of this exciting area. Abstract : The controlled synthesis of π‐conjugated polymers was discovered nearly 15 years ago. Since that time, the importance of metal catalysts and how they play a role in controlling the polymerization process has become an active area of research. This Minireview highlights some of the general features of metal complexes used in catalyst‐transfer polycondensation (CTP), the typical monomers that can be polymerized and, describes a few potential avenues for future exploration.